The experience machine : how our minds predict and shape reality - Clark, Andy, 1957- (Pantheon Books, 2023)
"A grand new vision of cognitive science that explains how our minds build the world, learn from it, and sometimes deceive themselves For as long as we've studied the mind, we've believed that our senses determine what our mind perceives. But as our understanding of neuroscience and psychology has advanced in the last few decades, a new view has emerged that has proven to be both provocative and hugely powerful-that the mind is not a passive observer, but an active predictor. At the core of this research is the radical reimagination of the way our brains process sensory information. Now this new school of "predictive processing" is arguing that we anticipate what we will see before we process the experience. Only then does our brain compare its prediction to the sensory information. At the forefront of this research is widely acclaimed philosopher Andy Clark, who has synthesized his revolutionary work on the predictive brain to explore its fascinating mechanics and implications. The most stunning of these is the realization that experience itself, because it is guided by prior expectation, is a kind of controlled hallucination. From the most mundane experiences to the most sublime, it is the mind that shapes most of our reality. Encountering errors in prediction helps us learn and makes us confident experts, but predictive feedback loops can also lock in conditions like chronic pain, addiction, and anxiety. A landmark study of cognitive science, The Experience Machine is a grand vision that sketches the extraordinary explanatory power of the predictive brain for our lives, health, world, and society"--